2020
DOI: 10.2174/1574884714666191122103953
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Self-Medication Practices in India: A Systematic Literature Review and Meta-Analysis

Abstract: Background: Self-medication (SM) is a practice of using medications to treat the self-diagnosed symptoms without legitimate prescription by a health care professional. Alongside posing burden on to a patient, SM practices are associated with certain unfavourable health conditions such as drug-resistance, adverse effects, drug-interactions, including death. Objective: To systematically review and quantify the prevalence of SM practices and its associated factors in India. Methodology: A comprehensive syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 27 publications
2
32
2
4
Order By: Relevance
“…The prevalence rate was in agreement with earlier studies done in Nepal for Pokhara (38.2%) and Morang (44.04%) (Paudel and Aryal, 2020;Parajuli et al, 2019). The studies done in India showed a prevalence rate of 53.57% (Rashid et al, 2020) and that for Yemen reported as 77.3% (Alshakka et al, 2019). The global prevalence rate was reported as 10% to more than 90% (Shaamekhi et al, 2019;Ayalew, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence rate was in agreement with earlier studies done in Nepal for Pokhara (38.2%) and Morang (44.04%) (Paudel and Aryal, 2020;Parajuli et al, 2019). The studies done in India showed a prevalence rate of 53.57% (Rashid et al, 2020) and that for Yemen reported as 77.3% (Alshakka et al, 2019). The global prevalence rate was reported as 10% to more than 90% (Shaamekhi et al, 2019;Ayalew, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…As relações da comunidade também interferem e influenciam no uso indiscriminado de medicamentos. Isso porque, em estudos, observa-se que a obtenção desses medicamentos é feita em farmácias, principalmente por orientação de farmacêuticos, além dos adquiridos por amigos e familiares ou pelo uso das sobras de prescrições anteriores (Ayalew, 2017;Khalifeh et al, 2017;Nepal & Bhatta, 2018;Rashid et al, 2020). É importante ressaltar que o risco de acontecer reações adversas por causa do uso de medicamentos sem aconselhamento e prescrição de um profissional adequado, com conhecimento na área, é extremamente potencializado.…”
Section: Resultsunclassified
“…In the current study, it is overwhelming to note a continuous decrease in self-prescription rate from 47% in 1985 to 16% in 2020. However, the rate of self-prescription is not constant in Indian region [14]. There are conflicting reports suggesting of 92%-11%self-medication in Delhi and Puduchery [15,16].…”
Section: Discussionmentioning
confidence: 99%